2022
DOI: 10.1021/acs.inorgchem.2c00059
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Nicotinamide Adenine Dinucleotide Regeneration with a Rhodium–Carbene Catalyst and Isolation of a Hydride Intermediate

Abstract: Regeneration of nicotinamide adenine dinucleotide (NADH) has been the primary interest in the field of enzymatic transformation, especially associating oxidoreductases given the stoichiometric consumption. The synthesized carbene-ligated rhodium complex [(η 5 -Cp*)Rh(MDI)Cl] + [Cp* = pentamethylcyclopentadienyl; MDI = 1,1′-methylenebis(3,3′-dimethylimidazolium)] acts as an exceptional catalyst in the reduction of NAD + to NADH with a turnover frequency of 1730 h −1 , which is over twice that of the higher cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…The 13 C{ 1 H} NMR spectra of the presented complexes show characteristic doublet signals in the range of 170-160 MHz with Rh-MIC coupling constants between J Rh;MIC = 53-48 Hz. [24,33] In the molecular structures in the crystal, the rhodium center in the complexes [Rh [34] The complexes show a η 5 mode from the Cp* ligand to the rhodium center with a metal-carbon bond length between 2.136(4)-2. [34] In contrast, an almost orthogonal geometry of the Cp* plane and the plane within the pyridyl-MIC coordination pocket (C1-N1-C4-N4) are observed in [Rh(CÀ N)H](PF 6 ) and [Rh(CÀ N)] (Figure 1).…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The 13 C{ 1 H} NMR spectra of the presented complexes show characteristic doublet signals in the range of 170-160 MHz with Rh-MIC coupling constants between J Rh;MIC = 53-48 Hz. [24,33] In the molecular structures in the crystal, the rhodium center in the complexes [Rh [34] The complexes show a η 5 mode from the Cp* ligand to the rhodium center with a metal-carbon bond length between 2.136(4)-2. [34] In contrast, an almost orthogonal geometry of the Cp* plane and the plane within the pyridyl-MIC coordination pocket (C1-N1-C4-N4) are observed in [Rh(CÀ N)H](PF 6 ) and [Rh(CÀ N)] (Figure 1).…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Recently, a [RhCp*] hydride complexes with a bis-NHC ligand (NHC = N-heterocyclic carbene) has been reported for the catalytic reduction of NAD + to NADH (= nicotinamide adenine dinucleotide) and crystallographically characterized. [24] However, very little information is available on their isolation and characterization, in particular with single crystal X-ray diffraction, and reactivity studies of such intermediates for complexes of pyridyl-MIC containing ligands. [25] The ligands (CÀ C = pyridyl-4-triazolylidene [26] and CÀ N = pyridyl-1-triazolylidene) [27] presented in this work show similar overall pÀ acceptor properties and a highly increased overall sÀ donor strength compared to the well-established bpy ligand.…”
Section: Introductionmentioning
confidence: 99%
“…24 Finally, in 2022, Yoon et al described a water-soluble carbene rhodium complex of formula [(η 5 -Cp*)Rh(MDI)Cl] + [MDI = 1,1′methylenebis(3,3′-dimethylimidazolium)] (Figure 1) as a catalyst for the reduction of NAD + to NADH, highlighting the evidence for the formation of a stable metal-hydride intermediate upon its isolation and characterization. 25 When studying the catalytic activity and cycle of [(Cp*)-Rh(bipy)Cl] + , Fish et al described the possibility of a reverse reaction, where NADH is oxidized to NAD + via the formation of a hydride complex. 7 Later, in 2012, Ru(II)-arene complexes containing bipyridyl bidentate ligands (Figure 1) were shown to oxidize NADH to generate NAD + .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Interestingly, Pizarro et al reported on Os­(II) complexes bearing picolinate N,O-chelates and studied their reactivity toward catalytic TH of pyruvate, producing quantifiable excess lactate inside cancer cells when using formate as the hydride source . Finally, in 2022, Yoon et al described a water-soluble carbene rhodium complex of formula [(η 5 -Cp*)­Rh­(MDI)­Cl] + [MDI = 1,1′-methylenebis­(3,3′-dimethylimidazolium)] (Figure ) as a catalyst for the reduction of NAD + to NADH, highlighting the evidence for the formation of a stable metal-hydride intermediate upon its isolation and characterization …”
Section: Introductionmentioning
confidence: 99%
“…Finally, in 2022, Sungho Yoon et al described a water-soluble carbene rhodium complex of formula [(η 5 -Cp*)Rh(MDI)Cl] + [MDI = 1,1′-methylenebis(3,3′-dimethylimidazolium)] (Figure 1) as catalyst for the reduction of NAD + to NADH, highlighting the evidence of the formation of a stable metal hydride intermediate upon its isolation and characterization. 18 When studying the catalytic activity and cycle of [(Cp*)Rh(bipy)Cl] + , Fish et al described the possibility of a reverse reaction, where NADH is oxidized to NAD + via formation of a hydride complex 3 . Later in 2012, Ru(II)-arene complexes containing bipyridyl bidentate ligands (Figure 1) were shown to oxidize NADH to generate NAD + 19 .…”
Section: Introductionmentioning
confidence: 99%